Background rates of 41 adverse events of special interest for COVID-19 vaccines in 10 European healthcare databases - an ACCESS cohort study. Issue 1 (4th January 2023) - Willame, C; Dodd, C; Durán, CE; Elbers, RJHJ; Gini, R; Bartolini, C; Paoletti, O; Wang, L; Ehrenstein, V; Kahlert, J; Haug, U; Schink, T; et al.
Highlights: We generated background incidence rates for 41 AESIs across a network of 10 European healthcare databases, which included a population of 63 million individuals. We highlighted the importance of the nature of the event and the setting in which it is diagnosed, which should be captured by the data banks that are used to calculate rates, otherwise underestimation is likely. The background incidence rates are used to monitor the safety of COVID-19 vaccines by the EMA, national health authorities and vaccine manufacturers. Abstract: Background: In May 2020, the ACCESS (The vACCine covid-19 monitoring readinESS) project was launched to prepare real-world monitoring of COVID-19 vaccines. Within this project, this study aimed to generate background incidence rates of 41 adverse events of special interest (AESI) to contextualize potential safety signals detected following administration of COVID-19 vaccines. Methods: A dynamic cohort study was conducted using a distributed data network of 10 healthcare databases from 7 European countries (Italy, Spain, Denmark, The Netherlands, Germany, France and United Kingdom) over the period 2017 to 2020. A common protocol (EUPAS37273), common data model, and common analytics programs were applied for syntactic, semantic and analytical harmonization. Incidence rates (IR) for each AESI and each database were calculated by age and sex by dividing the number of incident cases by the total person-time at risk. Age-standardized rates were pooled using random effect models according to the provenance of the events. Findings: A total number of 63, 456, 074 individuals were included in the study, contributing to 211.7 million person-years. A clear age pattern was observed for most AESIs, rates also varied by provenance of disease diagnosis (primary care, specialist care). Thrombosis with thrombocytopenia rates were extremely low ranging from 0.06 to 4.53/100, 000 person-years for cerebral venous sinus thrombosis (CVST) with thrombocytopenia (TP) and mixed venous and arterial thrombosis with TP, respectively. Interpretation: Given the nature of the AESIs and the setting (general practitioners or hospital-based databases or both), background rates from databases that show the highest level of completeness (primary care and specialist care) should be preferred, others can be used for sensitivity. The study was designed to ensure representativeness to the European population and generalizability of the background incidence rates. Funding: The project has received support from the European Medicines Agency under the Framework service contract nr EMA/2018/28/PE.